Understanding Pacing-Induced Cardiomyopathy: a mini review - Sidhi Laksono Purwowiyoto; Reynaldo Halomoan Siregar; Steven Philip Surya (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2021)
Patients with total atrioventricular block or sinus node dysfunction will need pacemaker implantation to improve the physiologic function of the heart.  It is known that chronic pacing such as right ventricular pacing could deteriorate the cardiac function (decreased left ventricular ejection fraction) due to dyssynchrony. This condition is knows as pacing-induced cardiomyopathy (PICM). The incidence of PICM could reach 19.5% during 3 years follow-up. The right ventricle is one of the locations for implantation. Chronic right ventricular pacing may cause interventricular dyssynchrony and disrupt the contraction mechanism in the heart. These will lead to cardiac remodeling and eventually impair the left ventricular function. Therapy is needed in patients with PICM to improve the symptoms and maintain the cardiac function. This article will further highlight the definition, mechanism, risk factor, treatment and preventive strategy for patients with PICM.